High-efficiency, high-energy ytterbium-doped Q-switched fibre laser with graphene oxide-COOH saturable absorber. (23rd May 2018) - Hou, Lei; Sun, Jiang; Guo, Hongyu; Lin, Qimeng; Wang, Yonggang; Bai, Yang; Lu, Baole; Chen, Haowei; Bai, Jintao
Abstract: Employing graphene oxide (GO)–COOH film as a new saturable absorber (SA), we demonstrate a high-efficiency, high-energy Q-switched ytterbium-doped fiber (YDF) laser operating at a wavelength of 1.03 μ m for the first time. GO–COOH film was prepared using a liquid-phase exfoliation method. Stable Q-switched pulses ranging from 4.5 μ s to 1.35 μ s with repetition rate in the range of 25 kHz–135 kHz were achieved. The maximum total output power was 82 mW, slope efficiency was 61.1% and the highest single pulse energy was 685 nJ at the repetition rate of 74 kHz—which is, to the best of our knowledge, the highest slope efficiency and largest pulse energy yet obtained from a Q-switched single-mode YDF laser with SA. The Q-switched YDF laser demonstrated in this paper confirms that GO–COOH is a cost-effective SA suitable for practical application in  ̃1.0 μ m Q-switched YDF lasers.